Diet composition and apparent digestibility in giant anteaters (Myrmecophaga tridactyla) kept under human care - Gentini, Thaís Moreira [UNESP]; Aragão Pereira, Fernanda Mara Macedo [UNESP]; da Silva, Lucas Batista [UNESP]; Hussni, Maria Fernanda [UNESP]; Mangueira, Danyele Karoline Avante [UNESP]; Testa, Carolyne Assis Eigerheer Pinke; de Cássia Gallo, Caroline [UNESP]; Carneiro, Lucas; de Lima Meirelles, Paulo Roberto [UNESP]; Okamoto, Priscylla Tatiana Chalfun Guimarães [UNESP]; Dierenfield, Ellen Sue; Melchert, Alessandra [UNESP] (Springer Nature, 2025)
Giant anteaters have limited biological knowledge and pose challenges in captivity, primarily due to their highly specialized feeding habits. This study aimed to evaluate the diet and its apparent digestibility in captive giant anteaters, seeking to understand the relationship between the offered diet and its utilization by animals under human care at institutions and zoos in the state of São Paulo. Seventeen adult giant anteaters (Myrmecophaga tridactyla), comprising 10 females and 7 males, were used to determine the nutritional composition of their diet, collect feces for bromatological analysis, and assess diet digestibility. The chemical composition of the offered foods and feces was evaluated, and the apparent digestibility of the diet was calculated. Analysis of the diets revealed that their nutritional composition did not differ significantly among institutions, despite variations in ingredient composition. The protein and lipid contents of the diets were as follows: 25.6% and 6.4% (diet 1), 34.7% and 10.9% (diet 2), 31.9% and 10.3% (diet 3), and 38.2% and 12.7% (diet 4), respectively. Ether extract (EE) had the highest apparent digestibility coefficient (ADC) (general mean 91 ± 4.8). The mean ADC was 68.9, 67.6, 79.6, and 89.9 for crude protein (CP); 89.8, 88.8, 92.5, and 94.2 for EE; 44.8, 64, 71.1, and 95.3 for nitrogen-free extract; and 80.5, 43.5, 43, and 87.1 for crude fiber, for diets 1, 2, 3, and 4, respectively. It is concluded that diets at São Paulo institutions showed good digestibility, especially for crude protein and ether extract. However, most animals had soft feces, indicating room for improvement. Energy intake affected body condition, emphasizing the need for tailored diets. Ether extract should not exceed 10%, and diets should provide 75–100% of maintenance energy, with regular monitoring of body condition scores.